Cognitive impairment and cortical reorganization in children with benign epilepsy with centrotemporal spikes. Issue 3 (7th January 2013) - Datta, Alexandre N.; Oser, Nadine; Bauder, Florian; Maier, Oliver; Martin, Florence; Ramelli, Gian Paolo; Steinlin, Maja; Weber, Peter; Penner, Iris‐Katharina
Summary Purpose Benign epilepsy with centrotemporal spikes (BECTS) is associated with mild cognitive deficits, especially language impairment. This study aimed to clarify whether children with BECTS with left‐ or right‐hemispheric, or bilateral focus have specific neuropsychological language deficits when compared to healthy controls, whether these deficits correlate functionally with language network organization (typical vs. atypical), and whether cofactors such as duration, handedness, and medication have a relevant impact on language reorganization processes. Methods Twenty‐seven patients and 19 healthy controls were examined with several neuropsychological tests (German version of the Wechsler Intelligence Scale for Children [WISC‐IV], Regensburger verbal fluency test [RWT], Corsiblock forward and backward and Hand‐Dominanz‐Test [HDT]) and with two language paradigms on functional magnetic resonance imaging (fMRI): silent reading of word‐pairs and silent generation of simple sentences. Key Findings Although neuropsychological test results only differed by trend between BECTS patients and controls, language laterality indices (LIs) in fMRI were significantly lower in patients than in controls. In particular, the anterior language network with Broca's area and the supplementary motor area (SMA) revealed the lowest LIs and showed the most bilateral or right hemispheric activations in the sentence generation task. Medication and duration of epilepsy did not have any significant effect on language reorganization and patients' performances. Significance Language reorganization in BECTS patients takes place in bilateral or right hemispheric language networks, with a strong focus in anterior language regions. These functional changes can be interpreted as important compensatory strategies of the central nervous system (CNS) to stabilize cognitive, especially language performance.